2007
DOI: 10.1107/s0108768107037263
|View full text |Cite
|
Sign up to set email alerts
|

Compressed hydrogen-bond effects in the pressure-frozen chloroacetic acid

Abstract: The competing effects of squeezed OH...O bonds, destabilizing the H-atom position, and of displaced hydrogen donor and acceptor groups, favouring the ordered H-atom sites, have been tuned by pressure in the pressure-frozen dichloroacetic acid. Its structure has been determined at 0.1, 0.7, 0.9 and 1.4 GPa: in this pressure range the crystals are stable in the monoclinic space group P2(1)/n. The molecules are O-H...O hydrogen bonded into dimers, which in turn interact via a unique pattern of halogen...halogen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…These data confirm the role of ClÁÁÁH contacts in the molecular association in crystal. Analogous contacts have been observed in simple halogenated alcohols [18][19][20][21][22].…”
Section: Molecular Parameterssupporting
confidence: 63%
“…These data confirm the role of ClÁÁÁH contacts in the molecular association in crystal. Analogous contacts have been observed in simple halogenated alcohols [18][19][20][21][22].…”
Section: Molecular Parameterssupporting
confidence: 63%
“…1 High pressure does not change this preference in formic and acetic acids. 44,45 However, chloroacetic acid forms R 2 2 (8) dimers, 46 while bromochlorofluoroacetic acid aggregates into zigzag catemers and dimers depending on the pressure of crystallization. 47 The unit-cell compression up to 2.21 GPa (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the electron density distribution of the halogen atom presents a ''polar flattening'' has been proposed by Gajda and Katrusiak [20,79,80] based on a X-ray study of dichloroacetic acid under pressure. It was observed that one of the ClÁÁÁCl distances (the most linear one) decreases from 3.813 Å (0.1 GPa) to 3.442 Å (1.4 GPa).…”
Section: Monomersmentioning
confidence: 99%